STRENGTHENING HUMAN RESOURCES GOVERNANCE ON PROGRAM SUCCESS DISTRIBUTION AND DEVELOPMENT OF BEEF IN JAMBI PROVINCE, INDONESIA - Maruli P.; Firmansyah; Hoesni F.; Afriani H. (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
This study aims to analyze the influence of human resource governance and model for strengthening human resources governance in the program the spread and development of cattle that can increase the production and income of farmers in Jambi Province.The research method used is a survey method with a stratified random sampling technique consisting of 3 strata. Data analysis used path analysis andmodel using Analytical Hierarchy Process. Farmers are not fluent in returning livestock to the pattern of cattle noise in several districts in Jambi Province (37.49%), then quite a lot of them are also able to smoothly return livestock (35.57%), and only a small percentage fluent (10.27%). Prospect and Payment partially affectk the welfare of farmers in the local government's cattle rowing pattern program, while Return and Repayment partially affect the success of the regional government's cattle rowing pattern program.